2009
DOI: 10.1111/j.1600-0854.2008.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomal Targeting of PTS2 Pre‐Import Complexes in the Yeast Saccharomyces cerevisiae

Abstract: †These authors contributed equally to this work.Posttranslational matrix protein import into peroxisomes uses either one of the two peroxisomal targeting signals (PTS), PTS1 and PTS2. Unlike the PTS1 receptor Pex5p, the PTS2 receptor Pex7p is necessary but not sufficient to target cargo proteins into the peroxisomal matrix and requires coreceptors. Saccharomyces cerevisiae possesses two coreceptors, Pex18p and Pex21p, with a redundant but not a clearly defined function. To gain further insight into the early e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…This localization suggested that Pex7p functions in a similar manner to Pex5p, only instead operating as an import receptor for newly synthesized PTS2-containing proteins. Gel-filtration chromatography has shown mammalian PEX7 to be monomeric (Mukai and Fujiki, 2006), consistent with MS analysis of S. cerevisiae PTS2 pre-import complexes which contain Fox3p (thiolase)/Pex7p/Pex18p in the following proportions 2:1:1 (Grunau et al, 2009). Although the structure of Pex7p is unknown, it is predicted to be a member of the β-transducinrelated (WD-40) protein family, forming a sevenbladed β-propeller, consisting of six WD repeats and a distinct N-terminal region.…”
Section: Pex7p Receptorsupporting
confidence: 65%
See 3 more Smart Citations
“…This localization suggested that Pex7p functions in a similar manner to Pex5p, only instead operating as an import receptor for newly synthesized PTS2-containing proteins. Gel-filtration chromatography has shown mammalian PEX7 to be monomeric (Mukai and Fujiki, 2006), consistent with MS analysis of S. cerevisiae PTS2 pre-import complexes which contain Fox3p (thiolase)/Pex7p/Pex18p in the following proportions 2:1:1 (Grunau et al, 2009). Although the structure of Pex7p is unknown, it is predicted to be a member of the β-transducinrelated (WD-40) protein family, forming a sevenbladed β-propeller, consisting of six WD repeats and a distinct N-terminal region.…”
Section: Pex7p Receptorsupporting
confidence: 65%
“…PTS2 proteins appear to bind to monomeric PEX7 (Mukai and Fujiki, 2006;Grunau et al, 2009), and there is some evidence to suggest that mammalian PEX7 only binds PEX5L in the presence of PTS2 cargo (Mukai and Fujiki, 2006). Furthermore, these authors suggest that the PTS2-PEX7 complex can only interact with PEX14 via PEX5L, consistent with the known docking function of the W-X 3 -F/Y motifs of PEX5.…”
Section: Stoichiometry Affinity and Order Of Binding Interactions Ammentioning
confidence: 73%
See 2 more Smart Citations
“…The solubilization of membrane proteins was followed by centrifugation at 100,000 ϫ g (Sorvall T-647.5) for 1 h at 4°C to remove insolubilized membrane proteins. Soluble and/or membrane-bound Gpd1p-TEVcs or Pex21p-TEVcs-Protein A complexes were purified as described earlier (42,43). The eluate of soluble Gpd1p complexes was subjected to size-exclusion chromatography using a Superose 6 PC3.2/30 column (GE Healthcare).…”
Section: Affinity Purification and Characterization Of Protein Complementioning
confidence: 99%